Clinician attitudes to pain and use of analgesia in cattle: where are we 10 years on? - Remnant, John G; Tremlett, Alex; Huxley, Jon N; Hudson, Chris D (BMJ Publishing Group, 2017)
Pain in cattle can arise though disease or injury or may result from veterinary or husbandry procedures. Controlling pain is important to safeguard animal welfare. Previous studies indicated that the use of analgesics in cattle has lagged behind use in companion animals. Over the last decade, more analgesic products have become available for use in cattle and there have been increased efforts to communicate the importance and benefits of analgesia. A questionnaire (based on that used in a similar study published in 2006) was sent to UK cattle practitioners asking them to score pain severity for several conditions of cattle and asking about their attitudes towards and use of analgesic medicines. A total of 242 surveys were returned. Male clinicians and those graduating before 1990 scored pain severity significantly lower and were significantly less likely to use NSAIDs. Generally, use of NSAIDs was more common for conditions assigned higher pain scores. However, uptake of NSAID use was much lower for a number of routine procedures in calves than would be expected from the pain scores they were assigned. A need remains to increase use of analgesic products, especially NSAIDs in calves, in line with best practice recommendations.